Гельминтофауна бычка травяника Zosterisessor ophiocephalus водоемов Северо-западного Причерноморья - Квач, Ю. (Екологічна безпека прибережної та шельфової зон та комплексне використання ресурсів шельфу, 2005)
Приведены современные данные по гельминтофауне бычка травяника в Одесском заливе и лиманах Северо-Западного Причерноморья, которая составила 13 видов. Впервые у бычка травяника найдены четыре вида паразитов: Proteocephalus subtilis, Аsymphylodora pontica, Raphidascaris sр. 1., Streptocara crassicauda 1. Гельминтофауна бычка травяника исследованного района наиболее похожа на таковую из Азовского моря, что вызвано сходством гидрологического и гидрохимического режимов этих акваторий. Current data on helminth fauna of a grass goby in Odessa Bay and limans of the northwestern areas of the Black Sea constituting 13 species is presented. For the first time four species of parasites are found in the grass goby: Protocephalus subtilis, Asymphylodora pontica, Raphidascaris sp. 1., Streptocara crassicauda 1. Helminth fauna of the grass goby of the investigated region resembles the one from the Sea of Azov that is caused by similarity of hydrological and hydrochemical regimes of these areas.